Suami dan Tanggung Jawab Terhadap Istri dalam Iddah: Sebuah Kajian Analisis Yuridis - Musyrifa S; Saharuddin Saharuddin; Ardiyanti Aris (Jurnal Litigasi Amsir, 2024)
This research aims to investigate how husbands fulfill their responsibilities towards wives during the iddah period and identify the challenges that arise in the implementation of the husband's responsibilities towards the wife during iddah. The research employs both normative and empirical approaches, including legal, case, and social approaches. The findings reveal that the husband's responsibilities towards the wife during iddah in civil law, including in Indonesia, encompass crucial aspects such as mut'ah alimony, madhiyah alimony, child support, dowry, and the division of shared assets. Law Number 1 of 1974 (c) provides the legal basis to obligate former husbands to provide financial support to their ex-wives. The primary challenges lie in economic issues, where some husbands may be unable to pay iddah alimony, coupled with a lack of understanding and awareness among involved parties regarding the legal resolution process. Therefore, efforts are needed to enhance public awareness regarding rights and obligations in this situation to facilitate the resolution of emerging issues.